Pranayama Nadi Sodhana untuk Meredakan Overthinking - Ni Made Riska Yulianti; Made G. Juniartha (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
Overthinking is an act of overthinking something for a long time. Overthinking can be done by anyone, both young and old. This study was conducted to determine the causes and effects of overthinking, along with appropriate pranayama to relieve it. This research is a qualitative research using the literature review method and modified with the opinions and thoughts of the author. Overthinking is caused by many factors, both internal and external, such as a lack of ability to manage negative emotions and negative thoughts that arise, an unsupportive environment and unpleasant past experiences, as well as problems in life. Overthinking can interfere with physical and psychological health, such as stress and anxiety, insomnia, headaches, digestive system disorders, as well as hypertension and heart disease. Overthinking can be relieved by concentration and relaxation through pranayama nadi sodhana.Keywords : overthinking, pranayama, nadi sodhana, yoga